Climate Resilience in Asia’s Mega Deltas: A Spatial Approach to Adaptation Planning - Nelson, Katherine (Asian Development Bank, 2025)
The article explores a spatial and food systems approach to adaptation planning in Asia's mega-deltas, such as the Mekong and Ganges-Brahmaputra, which are severely threatened by climate change and jeopardize food security. The research identifies vulnerability hotspots and recommends a comprehensive strategy that includes investing in capacity building, modernizing irrigation infrastructure, and promoting climate-resilient agricultural practices like crop diversification to boost farmer incomes and overall resilience.